THE USE OF HETEROTROFIC BACTERIA FOR GROWTH AND SURVIVAL RATE OF TILAPIA SALINE (Oreochromis niloticus) - Tri Emrinelson; F. Feliatra F. Feliatra; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe heterotrophic bacterial isolate used came from the collection of the Marine Microbiology Laboratory, Department of Marine Sciences, University of Riau. This research aims to look at the effect of feeding fish mixed with heterotrophic bacteria on survival rate, absolute weight growth, heterotrophic bacterial counts and water quality. This research was conducted in May - June 2019. This research used an experimental method with a Completely Randomized Design (CRD), carried out four levels of treatment with three replications. The treatments given were P0 without the addition of bacterial isolates, P1 addition of isolate J, P2 addition of N isolates and P3 addition of all isolates. The results showed the level of life graduation obtained a value of P> 0.05, ie there was no effect of the addition of bacterial isolates to the level of survival rate. The growth of absolute weight is influenced by the addition of bacterial isolates with a P value <0.05 and the highest average is at P3 of 6.09 g. In the measurement of bacterial isolate water quality did not give effect, but the water quality is still optimal for fish maintenance with temperatures between 27-28ºC, pH between 7.0-8.0, DO between 3.8 - 4.5 mg / l, and ammonia 0.70-1.82 ppm. Keywords: Heterotrophic Bacteria, Survival Rate, Tilapia Saline (Oreochromis niloticus), Weight Growth.